A Comparative study on the S- values of cow and buffalo ghee calculated using equations specified in ISO (17678) method of determining the milk fat purity by gas chromatographic analysis of triglycerides. - Sharma, Vivek; Rao, Priyanka Singh; Arora, Sumit; Naik, Laxamana; Sihag, Manvesh; Meghwal, Karuna; Kumar, Kuldeep (Indian Journal of Dairy Science, 2021)
Cow and buffalo ghee samples were prepared from the milk collected from the locations in eastern, western, southern, and northern parts of the country. Ghee prepared so was subjected to triglyceride analysis using gas-liquid chromatography and S- limits were calculated using the equations specified in the ISO method. All the five S- limits, as specified in the standard for cow milk, got deviated on both the lower and upper side of the limits in the case of the cow as well as buffalo ghee samples of all four regions.Â Buffalo ghee samples were found to have a higher upper S- total (ST) limit ranging from 109.34 to 118.21 in the samples from all four regions, whereas lower value was slightly less (94.06 to 94.59) than the lower range specified in the standard for buffalo ghee samples from eastern, northern and southern region samples. A similar trend was observed in the case of s- limit (S4) specified for the detection of Palm oil and beef tallow. In cow ghee also the S- values showed a trend of deviation from the standard.